Borrowing by Subnational Governments : Issues and Selected International Experiences - Ter-Minassian, Teresa (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1996)
This paper presents various models of control with advantages and disadvantages, the balance of which would make it more or less suitable to a particular country's circumstances. As these circumstances evolve-as fiscal and macro imbalances improve or worsen-the preferable model may change over time. Although appealing in principle, sole reliance on market discipline for government borrowing is unlikely to be appropriate in many circumstances. This is so, because one or more of the conditions for its effective working frequently are not realized in each particular country. The increasing worldwide trend toward devolution of spending and revenue-raising responsibilities to subnational governments seems likely to come into growing conflict with systems of administrative controls by the central government on subnational borrowing. Rules-based approaches to debt control would appear preferable, in terms of transparency and certainty, to administrative controls and also to statutory limits defined in the context of the annual budget process, the outcome of which may be unduly influenced by short-term political bargaining.